1992
DOI: 10.1162/jocn.1992.4.2.155
|View full text |Cite
|
Sign up to set email alerts
|

Modes of Lexical Access in the Callosotomized Brain

Abstract: Left hemisphere processing is typically characterized as analytic and serial whereas the right hemisphere is characterized as wholistic and parallel. Word recognition may be an exception to this dichotomy if the letter-by-letter alexia produced by left hemisphere damage reflects the reading abilities of the right hemisphere. We investigated this possibility by studying prelexical and lexical processes in the separated hemispheres of callosotomy patient J. W. A word superiority effect demonstrated in each visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
2
4

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 32 publications
(37 reference statements)
6
43
2
4
Order By: Relevance
“…In their view, nonwords in either VF are recognized via the slow, serial process and thus show length effects. This view has been supported by an experiment with a split-brain patient (Reuter-Lorenz & Baynes, 1992). Other hemispheric length effects have been observed in nonpronounceable letter strings, suggesting that the LH is more efficient than the RH in processing local elements of a display (Eng & Hellige, 1994).…”
Section: Discussionmentioning
confidence: 83%
“…In their view, nonwords in either VF are recognized via the slow, serial process and thus show length effects. This view has been supported by an experiment with a split-brain patient (Reuter-Lorenz & Baynes, 1992). Other hemispheric length effects have been observed in nonpronounceable letter strings, suggesting that the LH is more efficient than the RH in processing local elements of a display (Eng & Hellige, 1994).…”
Section: Discussionmentioning
confidence: 83%
“…To investigate this claim, words and nonwords were presented to the left or right of fixation at eccentricities that placed them either entirely in foveal locations (with medial edges 0.25º from fixation) or entirely in extrafoveal locations (with medial edges 2.20º from fixation). As in some previous studies of hemispheric asymmetry, performance in each location was assessed using the Reicher-Wheeler task (after Reicher, 1969, andWheeler, 1970) to provide an assessment of the wordnonword effect and LH dominance for word recognition that would not be contaminated by perceptual asymmetry and guesswork (see, e.g., Jordan et al, 1998Jordan et al, , 2000Reuter-Lorenz & Baynes, 1992). 2 An eyetracking system linked to a computer-controlled, fixation-contingent display ensured accurate fixation when each word was presented.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, when stimuli are presented briefly, observers are more likely to encode information from words than from nonwords, which, in turn, produces a processing advantage for word stimuli. Moreover, other studies using similar displays of words and nonwords but presented as extrafoveal lateralized displays (e.g., Jordan et al, 2000;Reuter-Lorenz & Baynes, 1992) have reported that word-nonword effects occur when stimuli are projected to the LH, but are absent (or greatly reduced) when stimuli are projected to the RH. Thus, when stimuli are presented in lateralized displays outside foveal vision, only stimuli projected to the LH produce a substantial word-nonword effect, because only these stimuli directly activate LH processes specialized for word recognition.…”
mentioning
confidence: 96%
“…Studies of picture processing in the two hemispheres provide an interesting counterpart to studies of word processing for a number of reasons. First, the use of pictures circumvents the concerns raised by left hemisphere dominance for word recognition [47,57] and for language processing more generally. Levine and Banich [41] showed, for example, that while the typical left hemisphere advantage is observed for word reading, no lateralized differences are found for the naming of pictures of the same objects (see also Experiment 1 of Biederman and Cooper [4]).…”
Section: Introductionmentioning
confidence: 99%